The IAEA electronic stopping power database: Modernization, review, and analysis of the existing experimental data - Montanari, Claudia Carmen (2024)
We review the electronic stopping power data within the IAEA database, assessing the abundance and scarcity of available data as a function of energy and collisional systems. Our analysis includes an examination of the experimental values, their evolution in time, the dispersion among data, and trends of the more recent measurements. Additionally, we provide comparisons with SRIM-2013 calculations for select cases of interest. Notably, we identify sparsely measured systems and energy regions, emphasizing the pressing need for new, reliable data and independent theoretical predictions.